PUSAT OLAHRAGA PANAHAN BANJARBARU - Cahyadi, Arif; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
An Archery sports center is a place to accommodate various types of archery activities with a wider scope. The design focuses on the goal of building facilities to develop the sport. The existence of this goal is based on the problem of the archery room that can threaten the environment. To overcome this, we need a design that is recreational, has educational value and provides a place to compete. By using a programmatic architectural approach, an architect will find it easier to analyze and create a more representative archery design.